2014
DOI: 10.1007/s12221-014-2160-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wood species and particle size on mechanical and thermal properties of wood polypropylene composites

Abstract: This study aims to investigate the effects of two types of wood flour; oil palm mesocarp flour (OMF) and rubberwood flour (RWF), and their particle sizes on mechanical, physical, and thermal properties of wood flour reinforced recycled polypropylene (rPP) composites. The composite materials were manufactured into panels by using a twin-screw extruder. The rPP composites based on RWF significantly showed higher flexural, tensile, and compressive properties (both strength and modulus) as well as hardness and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…It can be observed that the TPNR composites based on RWS 80 mesh (line (E)) degraded at 362.8°C with 20% weight loss, while the degradation of the composites based on RWS 40 mesh (line (C)) occurred with 20% weight loss at 365.5°C. This finding is in good agreement with Ratanawilai et al [13], who found that the particle sizes insignificantly affected the thermal stability of wood-plastic composites. In fact, the chemical constituents (e.g., cellulose, lignin, and hemicelluloses) of wood as well as their contents mainly affect the thermal stability of wood sawdust [13,23,25], which the particle size influences lightly.…”
Section: Thermal Degradation Behavior Of Tpnr and Tpnr/rwssupporting
confidence: 92%
See 3 more Smart Citations
“…It can be observed that the TPNR composites based on RWS 80 mesh (line (E)) degraded at 362.8°C with 20% weight loss, while the degradation of the composites based on RWS 40 mesh (line (C)) occurred with 20% weight loss at 365.5°C. This finding is in good agreement with Ratanawilai et al [13], who found that the particle sizes insignificantly affected the thermal stability of wood-plastic composites. In fact, the chemical constituents (e.g., cellulose, lignin, and hemicelluloses) of wood as well as their contents mainly affect the thermal stability of wood sawdust [13,23,25], which the particle size influences lightly.…”
Section: Thermal Degradation Behavior Of Tpnr and Tpnr/rwssupporting
confidence: 92%
“…Because the wood had more degradation than the HDPE, thus, the increasing addition of wood into the composites reduced the thermal stability. Likewise, stronger interfacial adhesion between the wood sawdust and the polymer matrix increased the thermal stability [13,23]; an addition of sawdust content in the polymer composites resulted in poorer interfacial bonding between phases of the materials.…”
Section: Thermal Degradation Behavior Of Tpnr and Tpnr/rwsmentioning
confidence: 99%
See 2 more Smart Citations
“…With fast growth in the global market share recently, wood plastic composites (WPCs) are emerging as green composite materials that combine the advantages of wood and thermoplastics, for example, long-term performance, cost-effectiveness, shape flexibility, and small carbon footprint (Ashori 2008;Naumann et al 2012). Wood plastic compounds are extensively employed in interior and exterior applications, such as building, housewares, automobile components, and various structural members (Muller et al 2013;Ratanawilai et al 2014).…”
Section: Introductionmentioning
confidence: 99%